Phylogeny and cocoon production in the parasitic leech Myzobdella lugubris Leidy, 1851 (Hirudinidae, Piscicolidae) - Saglam, Naim; Saunders, Ralph; Lang, Shirley A.; Shain, Daniel H. (Walter de Gruyter Gmbh, 2018)
Myzobdella lugubris is a commensal leech on crustaceans and a parasite to fishes, surviving predominantly in brackish waters throughout North America. Specimens in this study were collected within the tidal zone of the Delaware River basin (New Jersey and Pennsylvania). To compare regional M. lugubris specimens, defined characters were scored after dorsal and ventral dissections, and phylogenetic relationships were resolved using cytochrome c oxidase subunit 1 (CO1), 12S ribosomal RNA (rDNA) and 18S rDNA gene fragments. Variance between regional populations was low, suggesting recent dispersal events and/ or strong evolutionary constraints. The reproductive biology of M. lugubris was explored by quantitative analysis of secreted cocoons. Specimens produced 32.67 +/- 4.50 cocoons with fertilization ratios of 88.1% and hatching times of 48 +/- 7 days at 17 degrees C under laboratory conditions. At 22 degrees C, 46 +/- 28 cocoons were produced with fertilization ratios of 70.27% and hatching times of 28 +/- 5 days. Surprisingly, each cocoon supported only one embryo, which is unusual among oligochaetes.
Keywords: Reproduction; oligochaete; channel catfish; crustacean